Religion and Politics in Thirty Days: A Case Study of Bosnia and Herzegovina = Vera in politika v tridesetih dneh: študija primera Bosne in Hercegovine - Filandra, Šaćir (Edinost in dialog, 2023)
The subject of research in this paper is the relationship between religion and politics in the current Bosnian moment. The research sample is limited to the appearance and analysis of cases/examples of the relationship between religion and politics in a period of one month of the current year. More precisely, from the end of January to the end of February 2023. The paper follows and analyzes the dynamics of three characteristic phenomena of the relationship between religion and politics in the public space, with an emphasis on the relationship between religious themes and political actors.